As faces do autor: autoralidade nos discursos de Claudio de Moura Castro - Baptista, Carlos Alberto (2015)
This dissertation deals with the study of auctorialité in the discourses of economist Moura Castro. Since 1996, the economist publishes his opinion articles on Revista Veja, in which he usually handles Education matters and its economic implications. The position taken in his discourses are harshly criticized by educators, who consider them to observe the Education only under the economic optics, not connected to the teaching practice. It is created, then, a polemic image of the author that leads us to reflect on what allows a subject to pass through different knowledge areas and to have his discourse accounted for legitimate, even if his position contradicts other discourses inside the pedagogical field. The aims of this research are: to examine the auctorialité in this discourses and the implicated instances, through the production of subjectivity; to identify the construction of auctorialité in the opinion articles written by Moura Castro; to verify the positions from the Economy and Education fields related to the author s and enunciator s images. It is conducted an enunciative-discursive analysis, based on the theoretical and methodological postulations from french Discourse Analysis, supported by Maingueneau works. Auctorialité, inside this perspective, gives us the foundation to operate upon the projection and interaction of the enunciative instances, which act on this discourses, as well as upon positions and places that referred discourses establish. Therefore, we identify how the person, writer and the enunciator instances act on the maintenance of what the author assembles in the Moura Castro s opinion articles. Furthermore, the legitimacy of those discourses is founded on the values of a society in which the dominant myth of economic development turns the Economy into a supreme legitimacy science, while it integrates the Education as an associated instrument to this universal objective. Accordingly, the author position becomes decisive in the educational field, because when it is allied with the political-economic liberalism, begins to deliberate inside that field and to define it